Diffusion tensor imaging of the ankle as a possible predictor of chemotherapy induced peripheral neuropathy: pilot study - Gimber, Lana H.; Schwenk, Michael (Current problems in diagnostic radiology, 2019)
Purpose - Chemotherapy induced peripheral neuropathy (CIPN) is seen in up to 75% of treated cancer patients and can drastically limit their medical management and affect quality of life. Clinical and electrodiagnostic testing for CIPN have many pitfalls. Magnetic resonance neurography (MRN) is being increasingly used in the evaluation of peripheral nerves. Diffusion tensor imaging (DTI) shows promise in the workup of peripheral nerves. In this prospective pilot study, we investigated a possible relationship between DTI and peripheral neuropathy of the ankle and foot in cancer patients treated with chemotherapy. - Methods - Nine cancer patients with and without CIPN were clinically evaluated using vibratory perception threshold (VPT) testing. VPT score of >25Volts defined presence of CIPN. The posterior tibial nerve and branches in both feet were imaged using MRN and DTI. Fractional anisotropy (FA) and apparent diffusion coefficient (ADC) values were measured at the posterior tibial, medial plantar, and lateral plantar nerves. Measurements for the CIPN group were compared to without CIPN by VPT cutoff. Correlations and possible relationships between DTI parameters and CIPN were analyzed. - Results - A total of 16feet of 9 enrolled patients were imaged (9feet with CIPN and 7feet without CIPN). Average age was 60.6 ± 13.4 years (range: 33-74). Posterior tibial nerve ADC values were significantly lower than the medial plantar nerve ADC values in all feet (F = 3.50, P = 0.04). We found a correlation with FA and ADC values at specific nerve locations with CIPN, with the left medial plantar nerve FA value and left lateral plantar nerve ADC value demonstrating the strongest positive correlations (0.73 and 0.62, respectively). - Conclusions - The use of DTI for assessing CIPN is challenging but promising. This pilot study provides preliminary data showing correlations between FA and ADC measurements with CIPN and potential utility of DTI as a predictive marker of onset and severity of CIPN in the ankle and foot, which could aid in preventive strategies. Larger, prospective DTI studies are needed to draw definitive conclusions. - Clinical Relevance - MRN with DTI shows promising results as a potential predictive marker of CIPN in the ankle and foot.
Available online 6 January 2018
Gesehen am 30.04.2019